1999
DOI: 10.1517/13543784.8.12.2095
|View full text |Cite
|
Sign up to set email alerts
|

Aldose reductase inhibitors: therapeutic implications for diabetic complications

Abstract: The 'late complications' of diabetes mellitus, i.e., nephropathy, neuropathy and retinopathy are firmly rooted in inadequate control of blood glucose: hyperglycaemia. Hyperglycaemia causes elevated cytosolic glucose and/or rates of glucose metabolism, i.e., 'hyperglysolia,' within cells of vulnerable tissues. Although the molecular basis for the pathogenic effects of hyperglysolia remains to be proven, substantial evidence points to a key role for increased glucose metabolism through a cytosolic enzyme, aldose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
110
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(115 citation statements)
references
References 96 publications
3
110
1
1
Order By: Relevance
“…However, this contradicts numerous reports of (1) alleviation, rather than aggravation, of oxidative-nitrosative stress by AR inhibitors in other tissues of diabetic animals as discussed above, and (2) beneficial effects of both AR inhibitors and antioxidants on experimental DN [4,5,14,15]. Furthermore, several groups demonstrated that prevalence of DN depends on (1) erythrocyte AR content, and/or (2) frequency of the z-2 allele of the AR gene, in human subjects with diabetes mellitus [4,67,68]. Homozygosity for the z-2 allele in Type 1 (insulin-dependent) diabetes is associated with an increased expression of the AR gene and DN [67].…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…However, this contradicts numerous reports of (1) alleviation, rather than aggravation, of oxidative-nitrosative stress by AR inhibitors in other tissues of diabetic animals as discussed above, and (2) beneficial effects of both AR inhibitors and antioxidants on experimental DN [4,5,14,15]. Furthermore, several groups demonstrated that prevalence of DN depends on (1) erythrocyte AR content, and/or (2) frequency of the z-2 allele of the AR gene, in human subjects with diabetes mellitus [4,67,68]. Homozygosity for the z-2 allele in Type 1 (insulin-dependent) diabetes is associated with an increased expression of the AR gene and DN [67].…”
Section: Discussioncontrasting
confidence: 74%
“…Prospective Diabetes Study [3] strongly suggest the importance of hyperglycemia in the pathogenesis of chronic complications of diabetes mellitus including diabetic renal disease. Hyperglycemia leads to diabetic nephropathy (DN) via multiple mechanisms, and among them increased aldose reductase (AR) activity [4,5], nonenzymatic glycation and glycooxidation [6,7], activation of protein kinase C (PKC) and hexosamine pathway [8][9][10], arachidonic acid metabolism via 12/15-lipoxygenase pathway [11,12], and triose phosphate accumulation [13] are the best studied. Growing evidence obtained in diabetic animals (primarily, STZ (streptozotocin)-diabetic rats and mice) [14][15][16][17] as well as cell culture models [18][19][20] implicates free radicals and the potent oxidant peroxynitrite (a product of superoxide anion radical reaction with nitric oxide) in both hemodynamic and metabolic abnormalities leading to DN.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, sorbinil has been found not to prevent the development of diabetic retinopathy in dogs (29) or lessen its progression in patients (30). On the other hand, the frequency of an allelic variant of aldose reductase that confers increased expression of the gene (measured in white blood cells) is found to be significantly greater in diabetic patients with retinopathy than in those without retinopathy (31). Because retinal sorbitol levels in diabetic dogs were only minimally increased (in keeping with GHb elevated to only 8%) (29), one may speculate that the modest hyperglycemia did not lead to a degree of polyol pathway activation that would burden cells, and therefore there was little room for sorbinil to show a beneficial effect.…”
Section: Discussionmentioning
confidence: 99%
“…Aldose reductase (AR) reduces glucose to sorbitol with the aid of its cofactor NADPH, and sorbitol dehydrogenase (SDH), with its cofactor NAD + , converts sorbitol to fructose. In animal models, treatment with AR inhibitors (ARI) was shown to be effective in preventing the development of various diabetic complications, including diabetic retinopathy [108]. Although the exact mechanism is unknown, AR appears to be the possible link between increased polyol pathway activity and the development of some diabetic complications.…”
Section: Inhibition Of Increased Polyol Pathwaymentioning
confidence: 99%